2008
DOI: 10.1017/s0022112008002188
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry and transition to turbulence in a smooth axisymmetric constriction

Abstract: The flow through a smooth axisymmetric constriction (a stenosis in medical applications) of 75% restriction in area is measured using stereoscopic and time-resolved particle image velocimetry (PIV) in the Reynolds number range Re ~ 100–1100. At low Reynolds numbers, steady flow results reveal an asymmetry of the flow downstream of the constriction. The jet emanating from the throat of the nozzle is deflected towards the wall causing the formation of a one-sided recirculation region. The asymmetry results from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 36 publications
(62 reference statements)
5
55
1
Order By: Relevance
“…Vétel et al 7 116-1160 0 Ahmed and Giddens 6 500,1000 0 Griffith et al 8 50-2500 0 N/A 81D Sherwin and Blackburn 9 400-800 0 38 000 50D Griffith et al 12 1-400 0-5 200 000 31D Varghese, Frankel, and Fischer 11 Griffith et al 12 performed a numerical DNS study and showed that the discrepancy in the steady flow regime between the experimental results reported by Vétel et al 7 and the numerical investigations can be accredited to non-axisymmetric changes in the stenosis' shape, inherent in all experimental systems. However, the investigated Reynolds number ranged from Re = 1 to 400 and thus did not cover the non-stationary flow regime, nor was any stability analysis performed.…”
Section: Domain Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Vétel et al 7 116-1160 0 Ahmed and Giddens 6 500,1000 0 Griffith et al 8 50-2500 0 N/A 81D Sherwin and Blackburn 9 400-800 0 38 000 50D Griffith et al 12 1-400 0-5 200 000 31D Varghese, Frankel, and Fischer 11 Griffith et al 12 performed a numerical DNS study and showed that the discrepancy in the steady flow regime between the experimental results reported by Vétel et al 7 and the numerical investigations can be accredited to non-axisymmetric changes in the stenosis' shape, inherent in all experimental systems. However, the investigated Reynolds number ranged from Re = 1 to 400 and thus did not cover the non-stationary flow regime, nor was any stability analysis performed.…”
Section: Domain Sizementioning
confidence: 99%
“…This blockage ratio of 75% represents the threshold of clinical significance and visibility using present technology. 7 The radius can be written as…”
Section: A Problem Setupmentioning
confidence: 99%
“…Recently, Vetel et al 8 experimentally investigates transition to turbulence in a pipe geometry having a smooth axisymmetric constriction. When the Reynolds number is increased above the critical value of 200, an unsteady flow occurs with low-frequency oscillations of the reattachment point and the shedding of vortices.…”
Section: A Vortex Shedding Phenomenamentioning
confidence: 99%
“…The boundary and initial conditions, (8) and (9), are similarly transformed into computational coordinates through the use of (10). Thus, the boundary conditions at the bottom and top of the computational domain are…”
Section: Coordinate Transformationmentioning
confidence: 99%
See 1 more Smart Citation